Oneida, Nemaha County - Pfrang, Nicole (Kansas State University, The Chapman Center for Rural Studies, 2015)
This study explains the founding, growth, and decline of Oneida, due in part to railroad decline and the relocation of US Highway 36. It includes various interviews, early plat maps of the town, and photographs of early and present-day Oneida.
Nicole Pfrang, “Oneida, Nemaha County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/148.
Keywords: Oneida; Nemaha County; movie theater; drive-in; baseball; Highway 36